Pengaruh Pengetahuan, Sanksi, Kesadaran dan Kualitas Pelayanan Petugas Pajak Terhadap Kepatuhan Pajak - M. Fathrezza Imani; Imahda Khoiri Furqon (Department of Islamic Banking, Faculty of Islamic Economics and Business, UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
This research was conducted with the aim of analyzing the effect of Knowledge, Sanctions, Awareness and Service Quality of Tax Officers on Taxpayer Compliance. Data obtained through a questionnaire distribution survey and supported by the Regional Office or Regional Office of the Directorate General of Taxes. The analytical method used is descriptive quantitative. The test results show that partially Tax Knowledge has a significant effect on Taxpayer Compliance, Tax Sanctions have no significant effect on Taxpayer Compliance, Tax Officer Service Quality has no significant effect on Taxpayer Compliance, Taxpayer Awareness has no significant effect on Taxpayer Compliance.